AN EVALUATION OF COVERAGE OF TETANUS TOXOID VACCINE AMONG WOMEN OF CHILD BEARING AGE (15-45) YEARS: A COMMUNITY BASED SURVEY. : J Peop Univ Med Health Sci. 2025:15(3), 2-9. http://doi.org/10.46536/jpumhs/2025/15.03.651 - Veena Kumari1, Gotam Kumar2, Muhammad Siddique Rajput3, Ruqayya Ayoob Chandio4, Saifullah Mahar5, Sikender Arain6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2025)
BACKGROUND: Vaccination is one of the best general wellbeing drives in current period. It is in this manner, stressing to become familiar with the degree of under-immunization in Pakistan.Vaccine preventable sicknesses that have been effectively disposed of through the organization of antibodies increated nations lockjaw infection while Pakistan is as yet battling to builds inclusion of Lockjaw Pathogen inoculation among under 2 years and ladies of childbearing age. OBJECTIVE: This research study was intended to measure level of coverage for Tetanus toxooid vaccination among women of child bearing age of sindh. MATERIALS AND METHODS: The Cross-Sectional study was conducted among females in many Districts of sindh including urban and rural area through 4th year medical students of PUMHSW during one month. All females who were willing to participate in study were included in the study as respondent. Data collected on pre-designed structured questionnaire. DESIGN OF STUDY: Cross-Sectional. PLACE & DURATION: Various district of sindh, from August 2022 -to-November 2022. RESULTS: Total 300 females were studied regarding use of Tetanus Toxoid vaccine amongwomen of child-bearing age, out of then most of the females 70.7% were young with age groupof 25-35 years and out of all, 73 % have heard about TT vaccination, majority of females werenot aware about inclusion of TT vaccine in childhood and percentage was 59.7%. 65% female ofchild bearing age does not have knowledge about tetanus toxoid vaccine schedule during theirreproductive years, related to significance of TT vaccination most of females were aware (57%).According to the assessment of use of vaccine 55.3% women are willing to getvaccination during childbearing age while 75% had not gotten single dose of TT vaccinationduring childbearing age. CONCLUSION: It is revealed that the majority of female (child bearing age) were not vaccinated against Tetanus diseaes and their attitude was found to be good toward tetanus vaccination and they prefer to get vaccination during pregnancy. Tetanus Toxoid vaccination is useful vaccine in preventing tetanus for adult female if she completed all dosese of vaccination she will be protected for 20 years and she don’t need TT vaccination during their pregnancy through this approach we can prevent and control material and neonatal tetanus at grass root level